2021
DOI: 10.3390/agriculture11090812
|View full text |Cite
|
Sign up to set email alerts
|

A New Grafting Method for Watermelon to Inhibit Rootstock Regrowth and Enhance Scion Growth

Abstract: Grafting is a widely used technique in watermelon (Citrullus lanatus) production. However, cost of grafted seedlings is generally high as a result of intensive labor inputs for propagation using traditional grafting methods such as the manual removal of rootstock regrowth. This study developed a new grafting tool to physically remove the epidermis of pumpkin (C. maxima × C. moschata) and bottle gourd (Lagenaria siceraria) rootstock cotyledon base during grafting; we called this a new grafting method. Compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The push rod 9 is installed in the middle part of the base 7 through a slide rail pull head, and connected and fixed with the piston rod of the clip-pushing cylinder 6, so that the push rod 9 enters the clip-feeding slideway 2 and the clamping hand 1 through the support block 10 to push out the grafting clip. The working process is as follows: 1 The grafting clip opening moves forward from the vibrating feeder into the discharging row slideway at a certain speed to form a queue of inclined grafting clips; 2 Two discharging cylinders of the row-discharging part work alternately, and each time one grafting clip is discharged from the grafting clip queue into the clip-feeding slideway; 3 When the grafted seedlings are transported to the corresponding position for grafting, the clip-pushing cylinder extends out to drive the push rod to push the grafting clip into the clamping hand from the clip-feeding slideway, so that the grafting clip opening is opened; 4 The clamping cylinder is opened to drive the clamping hand to open, and the grafting clip breaks away from the clamping hand to clamp the grafted seedlings and complete the clamping action, then another round of clip-feeding operation is started.…”
Section: Structure and Working Principlementioning
confidence: 99%
See 2 more Smart Citations
“…The push rod 9 is installed in the middle part of the base 7 through a slide rail pull head, and connected and fixed with the piston rod of the clip-pushing cylinder 6, so that the push rod 9 enters the clip-feeding slideway 2 and the clamping hand 1 through the support block 10 to push out the grafting clip. The working process is as follows: 1 The grafting clip opening moves forward from the vibrating feeder into the discharging row slideway at a certain speed to form a queue of inclined grafting clips; 2 Two discharging cylinders of the row-discharging part work alternately, and each time one grafting clip is discharged from the grafting clip queue into the clip-feeding slideway; 3 When the grafted seedlings are transported to the corresponding position for grafting, the clip-pushing cylinder extends out to drive the push rod to push the grafting clip into the clamping hand from the clip-feeding slideway, so that the grafting clip opening is opened; 4 The clamping cylinder is opened to drive the clamping hand to open, and the grafting clip breaks away from the clamping hand to clamp the grafted seedlings and complete the clamping action, then another round of clip-feeding operation is started.…”
Section: Structure and Working Principlementioning
confidence: 99%
“…The models of the clip-pushing cylinder and clamping cylinder are SMC CDJ2RA16-85Z-B and AirTAC HFT0-20S, respectively. The design requirements of the push rod are as follows: 1 To reduce the deformation of steel ring or the damage to the clip body in the pushing process, the application point in clip pushing is located on the upper and lower sides of the rear part of the clip opening, to move away from the clip tail and the steel ring; 2 the opening angle of the grafting clip entering the clamping hand clip mouth reaches the maximum, so as to ensure that the grafted seedlings can smoothly enter the clip opening and be safely clamped; 3 the push rod moves smoothly to ensure a high success rate of clip pushing and feeding.…”
Section: Design Of the Clip-pushing Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that grafting caused bidirectional long‐distance transfer of messenger RNAs, microRNAs, and other small RNAs. Further studies revealed that sRNAs can induce epigenetic variation through an RNA‐directed DNA methylation pathway in recipient tissues of grafts, mostly altering cytosine methylation, occurring at both coding genes and transposons (Cerruti et al, 2021; Huang et al, 2021; Ince & Karaca, 2021; Liu et al, 2021; Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable grafting can effectively overcome the soil-borne diseases and insect pests caused by continuous cropping [1]. After grafting, the ability of a plant root system to absorb fertilizers and water is significantly enhanced, and the yield can be increased by 20-50% [2,3]; therefore, grafting technology is extensively applied in the world [4,5]. In the last two decades, the vegetable seedling cultivation industry in China has enjoyed rapid growth.…”
Section: Introductionmentioning
confidence: 99%